Commentary on: The potency of lncRNA MALAT1/miR-155 in altering asthmatic Th1/Th2 balance by modulation of CTLA4. Issue 5 (4th May 2020) - Foronjy, Robert
Abstract: Asthma is a common, allergic respiratory disorder affecting over 350 million people worldwide. One of the key features of asthma is skewing of CD4 + cells toward Th2 responses. This promotes the production of cytokines like IL-4 that induce IgE production resulting in the hypersecretion of mucus and airway smooth muscle contraction. Understanding the factors that favor Th2 expansion in asthma would provide important insights into the underlying pathogenesis of this disorder. Asthma research has focused on signaling pathways that control the transcription of key asthma-related genes. However, increasing evidence shows that post-transcriptional factors also determine CD4 + cell fate and the enhancement of allergic airway responses. A recent paper published by Liang et al. ( Bioscience Reports (2020) 40, https://doi.org/10.1042/BSR20190397 ) highlights a novel role for the long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) in Th2 development in asthma. MALAT1 modulates several biological processes including alternative splicing, epigenetic modification and gene expression. It is one of the most highly expressed lncRNAs in normal tissues and MALAT1 levels correlate with poor clinical outcomes in cancer. The mechanisms of action of MALAT1 in tumor progression and metastasis remain unclear and even less is known about its effects in inflammatory disease states like asthma. The work of Liang et al. demonstrates heightened MALAT1 expression in asthma and further shows that this lncRNA targets miR-155 to promote Th2 differentiation in this disease. This insight sets the stage for future studies to examine how MALAT1 manipulation could deter allergic immune responses in asthmatic airways.